KONSTRUKSI BANGUNAN TERKAIT POTENSI GEMPA DI INDONESIA (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The occurrence of an earthquake not only causes damage to infrastructure, but can also cause human casualties. Earthquake events are events that cannot be known with certainty when they occur and can occur in any area, so in this case it is necessary to anticipate to avoid damage to facilities and infrastructure and can cause casualties. For this reason, it is necessary to provide information so that the community will better understand earthquakes and what things must be considered to reduce the impact that may arise from an earthquake, especially for the construction community and the wider community related to building construction. By providing information about the potential for earthquakes in Indonesia to the construction community that the cause of damage to facilities and infrastructure after an earthquake is a building structure that does not comply with earthquake safety standards. The ability of buildings to withstand shocks caused by earthquakes is largely determined by the quality of buildings that meet earthquake-resistant building standards. Keywords : Earthquake, Building Construction, Earthquake Resistant Buildings